2020
DOI: 10.1002/jts.22626
|View full text |Cite
|
Sign up to set email alerts
|

What's in a Label? The Impact of Media and Sexual Assault Characteristics on Survivor Rape Acknowledgment

Abstract: Media coverage of sexual assault has increased since 2017 due to high‐profile cases and social media campaigns designed to increase awareness of sexual assault. The purpose of this study was to examine whether media coverage of the Harvey Weinstein allegations and the onset of the 2017 viral #MeToo movement impacted the likelihood of college women acknowledging their own victimization as rape. Participants were 207 female rape survivors who completed an online survey that included assessments of survivor ackno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…For example, if a person's conceptualization of rape is limited to the features of the "real rape" stereotype of an attack by a stranger using physical force, they will not identify a sexual intercourse coerced by a former partner exploiting the fact that they were drunk as a case of rape and are likely to answer "no" to the respective question (Cleere & Lynn, 2013;Hills et al, 2021). Consistent with this reasoning, several studies have shown that unacknowledged rape victims are more likely to endorse rape myths, label their experience as miscommunication rather than sexual assault, or experience rape by other means of coercion than the use of physical force (Dardis et al, 2021;Newins et al, 2021;Reed et al, 2020;Rousseau et al, 2020). Moreover, unacknowledged rape victims were shown to rate the probability of being raped to be significantly lower than acknowledged victims (Boyle & Walker, 2016).…”
Section: Unacknowledged Rape and Mental Constructions Of Rape And Con...mentioning
confidence: 97%
“…For example, if a person's conceptualization of rape is limited to the features of the "real rape" stereotype of an attack by a stranger using physical force, they will not identify a sexual intercourse coerced by a former partner exploiting the fact that they were drunk as a case of rape and are likely to answer "no" to the respective question (Cleere & Lynn, 2013;Hills et al, 2021). Consistent with this reasoning, several studies have shown that unacknowledged rape victims are more likely to endorse rape myths, label their experience as miscommunication rather than sexual assault, or experience rape by other means of coercion than the use of physical force (Dardis et al, 2021;Newins et al, 2021;Reed et al, 2020;Rousseau et al, 2020). Moreover, unacknowledged rape victims were shown to rate the probability of being raped to be significantly lower than acknowledged victims (Boyle & Walker, 2016).…”
Section: Unacknowledged Rape and Mental Constructions Of Rape And Con...mentioning
confidence: 97%
“…One limitation of the current study is that it was cross-sectional, and therefore, temporal relationships cannot be established. Despite the fact that acknowledgment status has previously been studied as a predictor of social reactions (Littleton et al, 2006), researchers have suggested acknowledgment is a “dynamic” process (Donde et al, 2018, p. 1735) and have noted that social reactions may influence acknowledgment status (Newins et al, 2021). As such, future studies should use longitudinal designs to better establish directionality and help to better understand how acknowledgment and social reactions may influence one another over time.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, social media has been used strategically to disclose experiences of sexual violence and to provide social support to survivors (Alaggia & Wang, 2020 ), though some studies find that survivors of sexual violence do not reap the same benefits of public sharing of experiences as much as individuals who experienced less stigmatized trauma, such as a natural disaster (Delker et al, 2020 ). Also, the survivors of sexual violence may interpret and identify their experiences differently based on prevalence of sexual violence cases in the media (Newins et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%